Clustering with One-Time Setup for Reduced Energy Consumption and Prolonged Lifetime in Wireless Sensor Networks - Heewook Shin; Sangman Moh; Ilyong Chung (International Journal of Distributed Sensor Networks)
In wireless sensor networks, clustering is effectively used for many applications, including environment monitoring, because it promises efficient energy consumption for inexpensive battery-operated sensors. The most famous clustering protocol, LEACH (Low Energy Adaptive Clustering Hierarchy), enables the balanced consumption of energy to prolong a network lifetime. In LEACH, however, extra energy and time are consumed to reform clusters at the setup phase of every round. This side effect is worse as the number of clusters increases. This paper presents a novel energy-efficient clustering scheme called COTS (Clustering with One-Time Setup) which removes the cluster-reforming process required at every round after the first round. The proposed COTS allows that the role of the cluster head is rotated among members in a cluster without cluster reforming. By removing the cluster-reforming process, the number of transmissions per round is decreased accordingly. As a result, energy consumption is significantly reduced, resulting in prolonged network lifetime. The simulation study shows that the network performance and lifetime are much improved as the number of clusters is increased.